Learner Leadership: A Change Agent for UK Interprofessional Learning - Cuthbert, K.; Glover, G.; Forman, Dawn (Palgrave MacMillan, 2015)
So what kind of leadership is appropriate for taking forward inter-professional learning (IPL) in the UK? This chapter will paint the UK IPL landscaper with commentary on IPL initiatives and their response to the steady progression towards differing patterns of care in the National Health Service (NHS). With a long-charted history in IPL and a significant volume of knowledge capital evaluating the impact of IPL models, the UK is on the cusp of an interesting threshold. How are we to realize the next wave of transformation on the UK IPL landscape, and does the current model of leadership help of hinder?